Filling in Marketing Mix Gaps: A TCCM-Framework Based Systematic Literature Review - Helena Louise Panggabean; Evi Noviaty (Jurnal Ekonomi, Manajemen, dan Bisnis, 2026)
This study presents a systematic literature review (SLR) on the evolution of marketing mix strategies over the past decade, with a focus on how traditional frameworks have been adapted in response to digital transformation, sustainability demands, and shifting consumer behavior. The review follows PRISMA guidelines and analyzes 54 peer-reviewed articles published between 2015 and 2025, sourced from Scopus and other reputable academic databases. The analysis employs the TCCM (Theory, Context, Characteristics, Methodology) framework to classify findings across theoretical foundations, research contexts, thematic focus, and methodological approaches.The results indicate that classical marketing mix models, particularly the 4Ps and 7Ps, remain dominant in both academic research and practical application, especially in emerging economies such as China, Indonesia, Malaysia, and Iran. Quantitative methodologies, particularly structural equation modeling, are still widely used; however, there is a growing shift toward mixed-method and qualitative approaches that provide richer contextual insights. Emerging themes include green marketing, digital marketing, artificial intelligence applications, and sustainability-oriented strategies, reflecting an expanding research agenda beyond traditional marketing boundaries.Despite these developments, several gaps remain evident, including limited theoretical integration, insufficient longitudinal research designs, and underrepresentation of specific sectors such as agriculture and cultural industries. This review synthesizes fragmented literature and proposes future research directions emphasizing theoretical pluralism, integration of Service-Dominant Logic and Dynamic Capabilities, and methodological innovation through big data analytics and experimental designs. Overall, this study provides a comprehensive synthesis that contributes to both academic development and managerial practice in evolving marketing environments.